“Caring for a Crisis”: Care and Control in Community Mental Health - Muusse, Christien; Kroon, Hans; Mulder, Cornelis Lambert; Pols, Jeannette (Frontiers in Psychiatry, 2022)
In the debate on coercion in psychiatry, care and control are often juxtaposed. In this article we argue that this dichotomy is not useful to describe the more complex ways service users, care professionals and the specific care setting interrelate in a community mental health team (CMHT). Using the ethnographic approach of empirical- ethics, we contrast the ways in which control and care take shape in situations of a psychiatric crisis in two CMHT’s: one in Trieste (Italy) and one in Utrecht (the Netherlands). The Dutch and Italian CMHT’s are interesting to compare, because they differ with regard to the way community care is organized, the amount of coercive measures, the number of psychiatric beds and the fact that Trieste applies an open door policy in all care settings. Contrasting the two teams can teach us how in situations of psychiatric crisis control and care interrelate in different choreographies. We use the term choreography as a metaphor to encapsulate the idea of a crisis situation as a set of coordinated actions from different actors in time and space. This provides two choreographies of handling a crisis in different ways. We argue that applying a strict boundary between care and control hinders the use of the relationship between caregiver and patient in care.